1982
DOI: 10.1007/bf02411236
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of45Ca incorporation with maturation ameloblast morphology in the rat incisor

Abstract: Rats were injected with 45Ca and horseradish peroxidase to determine the patterns of 45Ca incorporation into incisor enamel and the morphological types of the overlying maturation ameloblasts. 45Ca autoradiography showed no differences in the patterns of incorporation into enamel between routinely embedded and freeze-dried specimens. Enamel overlaid by ruffle-ended ameloblasts was much more heavily labeled while that overlaid by smooth-ended ameloblasts showed only moderate labeling. The observations lend furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 12 publications
1
35
1
1
Order By: Relevance
“…This is reasonable given that maturation ameloblasts modulate rapidly: one SA band moves to the next SA band through an RA band in 8-10 hours [23]. On the other hand, plasma membrane Ca 2+ -Mg 2+ -ATPase is enriched in RA but weak in SA [3], and in the part of the RA zone where the ruffled border of the RA is re-creating, calcium uptake in enamel is lacking [26], indicative of differential PMCA activity in maturation ameloblasts. Thus, the significance of a similar level of SERCA2 reactivity in RA and SA remains to be clarified.…”
Section: Resultsmentioning
confidence: 99%
“…This is reasonable given that maturation ameloblasts modulate rapidly: one SA band moves to the next SA band through an RA band in 8-10 hours [23]. On the other hand, plasma membrane Ca 2+ -Mg 2+ -ATPase is enriched in RA but weak in SA [3], and in the part of the RA zone where the ruffled border of the RA is re-creating, calcium uptake in enamel is lacking [26], indicative of differential PMCA activity in maturation ameloblasts. Thus, the significance of a similar level of SERCA2 reactivity in RA and SA remains to be clarified.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that AP-1 is regulatory for transcriptional factors induced by various stimuli, such as growth factors and UV irradiation (Angel and Karin 1991;Karin et al, 1997), it is suggested that amelo- blasts in the maturation zone of the rat incisor undergo active transcriptional regulation and, furthermore, that RA and SA undergo a different transcriptional regulation (Nishikawa 2000). The morphological characteristics of maturation ameloblasts support several functions, i.e., active or passive mineral transport and reabsorption followed by degradation of transitory enamel proteins, although matrix removal is performed in the early phase of the maturation zone (Takano et al 1982;Robinson et al 1995;Smith and Nanci 1995;Smith 1998). AP-1 in the ameloblast nuclei throughout the long maturation zone is therefore likely to relate to the elevation of mineral content in enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible regulatory transcriptional factor AP-1 components are, indeed, localized exclusively in the ameloblasts and papillary layer cells of the maturation zone of the rat incisor (Nishikawa 2000). During enamel maturation, calcium ions must pass through the enamel organ, which includes the ameloblasts, probably via nearby blood vessels (Takano et al 1982;Kawamoto and Shimizu 1997). Although it does not appear conclusive whether Ca 2 ϩ passes through ameloblasts by an intracellular or an intercellular route, several reports support the intracellular route for maturation ameloblasts (Hubbard 1995(Hubbard ,1996Kawamoto and Shimizu 1997).…”
mentioning
confidence: 99%
“…Perhaps both direct and indirect HRP flow occur through the SA layer into the enamel sur face. Accordingly, it is tempting to conclude that there is free permeation of tissue fluid between the papillary layer and the develop ing enamel surface through the SA layer and that the intercellular spaces of the SA layer have significance for the movements of metabolites, including ions, in the enamel organ, as has been suggested by recent auto radiographic and tracer studies [Kallenbach, 1980;Takano et al, 1982].…”
Section: Discussionmentioning
confidence: 99%